2017
DOI: 10.1161/strokeaha.117.017809
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α4 Overexpression on Rat Mesenchymal Stem Cells Enhances Transmigration and Reduces Cerebral Embolism After Intracarotid Injection

Abstract: ITGA4 overexpression on MSCs enhances transendothelial migration in vitro, but not in vivo, although it improves safety after intracarotid transplantation into stroke rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…In an instance of a hemophilia study, bone marrow derived MSCs transfected with human coagulation factor IX (hFIX) highly expressed hFIX with increased coagulation activity by 2.4-to 4.4-folds in contrast to other modified cells [103]. Genetic modification using Sox11, also results in enhanced migration of MSCs to a fractured bone site, speeding the healing process [104] while integrin α4 overexpression promoted transmigration, with a resultant reduced cerebral embolism [105]. Sox11 overexpression does not only increase the migration of MSCs but also the cell viability as well as their trilineage differentiation.…”
Section: Therapeutic Application Of Modified Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In an instance of a hemophilia study, bone marrow derived MSCs transfected with human coagulation factor IX (hFIX) highly expressed hFIX with increased coagulation activity by 2.4-to 4.4-folds in contrast to other modified cells [103]. Genetic modification using Sox11, also results in enhanced migration of MSCs to a fractured bone site, speeding the healing process [104] while integrin α4 overexpression promoted transmigration, with a resultant reduced cerebral embolism [105]. Sox11 overexpression does not only increase the migration of MSCs but also the cell viability as well as their trilineage differentiation.…”
Section: Therapeutic Application Of Modified Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The overexpression of PARKIN in MSCs was able to significantly reduce the expression of markers of cell death and oxidative stress, in addition to significantly reducing the production of reactive oxygen species (∼ 50% reduction) when compared to wild type and control groups (Bonilla-Porras et al, 2018). Studies in stroke models showed that MSCs overexpressing extracellular regulating kinase 1/2 or integrin A4 not only were able to show induction of neuronal differentiation, proliferation of neural stem cells and a significant functional recovery in mice after the treatment (Gao et al, 2019), but also demonstrated a significant decrease in cell aggregation and improvement of cerebral embolism in rats (Cui et al, 2017).…”
Section: Applications In Neurological Disordersmentioning
confidence: 99%
“…Both preclinical and clinical data revealed better outcome of intracortical cell delivery compared to intravascular delivery. 20,49,50 Methodological Limitations We included studies using different cell types, administration modes, et cetera, which increased the sample size for data analysis, particularly for clinical studies, and also enabled us to explore the sources of heterogeneity. 46 Proof-of-concept studies may be required to assess whether the advantage of intracortical delivery outweighs the safety concerns.…”
Section: Delivery Routementioning
confidence: 99%
“…No significant difference in therapeutic effect was found between studies using intra-arterial and intravenous delivery routes, but improper intra-arterial cell administration can trigger complications. 20,49,50…”
Section: Delivery Routementioning
confidence: 99%